Alternative policies for the control of air pollution in Poland - Bates, Robin (World Bank WashingtonUS, 1994)
Shows how appropriate economic incentives in the economy at large, and the use of specific economic instruments targeted at air pollution, can make an important practical contribution to sustainable development. Argues that, although free market forces alone may not achieve sustainable development, they can help us to make progress towards it through better resource management.